Thermodynamic Properties of Cyclophosphamide in Citric Acid Solution - Gao, Jinquan; Li*, Zongxiao; Zhao, Weiwei (Asian Journal of Chemistry, 2014)
The dissolution behaviors of cyclophosphamide in citric acid solution were studied by a microcalorimetric method, The measured integral and differential heat of solution was used to build equations of the solute and the heat, so that dissolution thermodynamic equations, Dsol Hm were achieved, The results show that, using the thermodynamic parameters of microcalorimetric method cyclophosphamide is simple and feasible. The method provides strong data support for the clinical application of cyclophosphamide.